Test-Retest Reliability of a Serious Game for Delirium Screening in the Emergency Department - Tong, Tiffany (Frontiers Media S.A., 2016)
Introduction: Cognitive screening in settings such as emergency departments (ED) is frequently carried out using paper-and-pencil tests that require administration by trained staff. These assessments often compete with other clinical duties and thus may not be routinely administered in these busy settings. Literature has shown that the presence of cognitive impairments such as dementia and delirium are often missed in older ED patients. Failure to recognize delirium can have devastating consequences including increased mortality (Kakuma et al., 2003). Given the demands on emergency staff, an automated cognitive test to screen for delirium onset could be a valuable tool to support delirium prevention and management. In earlier research we examined the concurrent validity of a serious game, and carried out an initial assessment of its potential as a delirium screening tool (Tong et al., 2016). In this paper, we examine the test-retest reliability of the game, as it is an important criterion in a cognitive test for detecting risk of delirium onset.